Application of information technologies in teaching of mathematics in Vilnius College in higher education - Saldauskienė, Jovita; Virkutis, Vytautas (Lietuvos matematikos rinkinys, 2002)
This work contains the material about forms and methods of teaching of mathematics. It contains clear description of the aims, terms, techniques and methods of teaching. The research was made. The analysis of students’ questionnaire datum was made. There were made the following conclusions: Mathematics teaching module in college in higher education is expedient to use emphasizing on practically applied subject. Mathematics computer programs are recommended as a more effective teaching method.